Relationship between mechanical properties of ceramic green body and structures of photo-cured acrylate polymer for ceramic 3D printing based on photo polymerization. Issue 3 (1st February 2021) - Lee, Hye-Ju; Park, Hye-Yeong; Kim, Eun-Hee; Choi, Hyun-Hee; Jin, Jungho; Choi, Jiyeon; Yang, SeungCheol; Jung, Yeon-Gil
Abstract: 3D printing technologies using photo polymerization of photo-curable monomer and oligomers as an organic binder have been studied to fabricate ceramics with a complicated shape. For minimizing distortion of ceramics during the manufacturing process and fast 3D printing of ceramic green body, high mechanical strength of ceramic green body and fast photo polymerization of the photo-curable resin are required, respectively. In this study, the ceramic green bodies with various compositions were fabricated by photo radical polymerization of the slurry-type resin composed of fused silica bead, and tri- or (and) mono-functional acrylate. Photo radical polymerization behaviors of mono-, tri-functional acrylate monomer, and blend of two monomers were analyzed by photo-DSC and FT-IR measurements. The structure analysis of photo-cured polymers made by each monomer was performed by thermo-mechanical analysis. Through mixing of mono- and tri-functional acrylate monomer, we confirmed that polymerization rate more increased compared with those of only mono-, tri-functional monomer. Unreacted vinyl groups in the polymers prepared with blend of two monomers decreased by an addition of mono-functional monomer in tri-functional monomer. The polymers prepared with the blend showed higher storage modulus and broader viscoelastic behavior compared to those fabricated with tri-functional monomer. Thus, to achieve high fracture strength of the green body, we verified that the photo-cured polymer in the green body should have high crosslinking density and low free volume based on reduction of unreacted vinyl groups in the polymer. Additionally, through analysis of cross-sectional SEM of the green body, we confirmed that acrylate monomer should include proper content in the slurry-type resin to maximize the fracture strength of the body regardless of the type of the used acrylate monomer. This was because low content of acrylate monomer in the slurry-type resin makes it difficult to form neckings composed with photo-cured polymers between the silica beads.